2006
DOI: 10.1111/j.1469-0691.2006.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-outbreak of Mycobacterium gordonae: usefulness of randomly amplified polymorphic DNA analysis to assess the clonality of the isolates

Abstract: Mycobacterium gordonae was detected in 18 of 21 clinical samples processed during the same day from patients with clinical suspicion of tuberculosis. Randomly amplified polymorphic DNA (RAPD) analysis revealed that all the isolates generated an identical pattern with each of the five primers used, and that these patterns were different from those of epidemiologically non-related isolates of M. gordonae. M. gordonae was not detected in the distilled water used for the procedures, and following replacement of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…4 Lastly, environmental contamination may represent an uncharacterized, but potentially important source of our M. gordonae, Mycobacterium terrae complex, Mycobacterium mucogenicum, and Mycobacterium scrofulaceum isolate reports. 4,30 This was the first population-based study of NTM prevalence using reports of isolation in the Southeastern U.S.; it includes a more racially diverse population than studies conducted in many other geographic sites. In addition, this study utilized reports from public and private clinical laboratories, collected demographic information about patients and reported the anatomic source and site of NTM isolation.…”
Section: Discussionmentioning
confidence: 99%
“…4 Lastly, environmental contamination may represent an uncharacterized, but potentially important source of our M. gordonae, Mycobacterium terrae complex, Mycobacterium mucogenicum, and Mycobacterium scrofulaceum isolate reports. 4,30 This was the first population-based study of NTM prevalence using reports of isolation in the Southeastern U.S.; it includes a more racially diverse population than studies conducted in many other geographic sites. In addition, this study utilized reports from public and private clinical laboratories, collected demographic information about patients and reported the anatomic source and site of NTM isolation.…”
Section: Discussionmentioning
confidence: 99%
“…RAPD typing showed that these isolates were identical and different from unrelated control strains. Environmental sampling in the laboratory did not yield M. gordonae, but after sterilization or replacement of all consumables and reagents, no more related M. gordonae isolates were detected (528). Similarly, a pseudo-outbreak of M. terrae was reported in Philadelphia, PA, where a laboratory noted that 14 cultures handled in a 6-day period were positive; all were from AFB-negative clinical samples and yielded growth only with the ESP liquid medium system but not on simultaneously inoculated Lowenstein-Jensen slants.…”
Section: Molecular Typing Of Nontuberculous Mycobacteriamentioning
confidence: 90%
“…RAPD has been claimed as a technique with low reproducibility, but we have the experience that, if strict conditions and criteria are followed, the obtained results can be considered useful for discrimination purposes (39)(40)(41). This technique also has the advantage of being easy to perform without complex equipment, such as that needed for other reference techniques like PFGE or complete-genome sequencing, so it can be performed in mediumsize laboratories like ours.…”
Section: Discussionmentioning
confidence: 99%